A busca da racionalidade nas escolhas orçamentárias organizacionais - Furtado, Robert Muzy (2018)
Purpose – The overall objective is to evaluate the implementation of SIIG/SAGE in the search for rationality in budgeting and overcoming incrementalism. In its specific objectives, the study aimed to analyze the variation of budgetary allocations in the planning of Fiocruz during 2001 to 2017 from the punctuated equilibrium theory perspective. To describe factors that influenced levels of stability and budget scores, and to examine the participation of SIIG/SAGE systems in the rational determinants present in the budget process. Design/Methodology – The research technique adopted was the case study, whose unit of analysis was the implementation of the SIIG / SAGE systems in the budgetary elaboration of Fiocruz. Two stages divide the research. First, internal documents data were tabulated using descriptive statistics tools then analyzed in light of the punctuated equilibrium theory. It allowed the identification of discrepant variations in annual budget allocations and their highlighted characteristics. In the second stage, data from structured interviews using content analysis confronted these variations, which revealed the rational determinants in the budget process and their relations with SIIG / SAGE. Findings – The results showed fundamental contributions of the SIIG and SAGE systems to the promotion of transparency, participation in the choices and standardization of the budget data. For the alignment of the budget with the strategy, performance analysis, monitoring and strategic communication, there were contributions, but in a more limited way, motivating the formulation of the proposals of this study. Practical implications – The research applicability is important to the organization since it evaluates the results obtained after the implementation of its key planning system. The institution’s internal community will be the largest beneficiary of this relevance. The proposals put forward may increase the budget process transparency level of in Fiocruz, communicating to the actors involved where and how the resources are being used. Social implications – The explanation of the factors that interfere in the budgetary choices of a public organization contributes to discuss the development of an efficiency culture in the public resources management, which can directly affect the quality of the expenses and services provided to society. Originality – To evaluate the effects of a recently deployed information system. Besides this, the analysis of the determinants that influence internal budget choices in a complex organization such as Fiocruz is a poorly explored field.